2019
DOI: 10.1177/0013124519856678
|View full text |Cite
|
Sign up to set email alerts
|

Injustice, Uselessness, and Illness: A Qualitative Study of Unemployed Graduates’ Lives in Iran

Abstract: Formal education in Iran, especially higher education, has been a means to smoothen the road to social mobility, provide good jobs, and boost people’s earnings. Now, being a university graduate and remaining unemployed is regarded as a challenge. In addition, governments consider this new unemployment a threat to their legitimacy. It seems that young unemployed graduates experience different problems in their social lives. This study aims to investigate the problems encountered by young unemployed graduates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…All interviews were transcribed verbatim and then translated from Farsi to English. Content analysis was used to analyze the collected written documents, materials, and participants’ responses (Bhattacherjee, 2012; Khezri et al, 2020; Mohajan, 2018). We identified patterns and key ideas behind the creation of participatory schools, as well as obstacles and reasons to oppose the philosophy of such schools.…”
Section: Methodsmentioning
confidence: 99%
“…All interviews were transcribed verbatim and then translated from Farsi to English. Content analysis was used to analyze the collected written documents, materials, and participants’ responses (Bhattacherjee, 2012; Khezri et al, 2020; Mohajan, 2018). We identified patterns and key ideas behind the creation of participatory schools, as well as obstacles and reasons to oppose the philosophy of such schools.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the unemployed graduate group, many studies have tried to canalize this issue based on statistics and recognize its major economic and social determinants. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the unemployed graduate group, many studies have tried to canalize this issue based on statistics and recognize its major economic and social determinants. 3,4 They have mostly explored graduate unemployment and work quantitatively at the macrolevel. At the microlevel, various studies have dealt with the live experiences of unemployed people in general as well as those of some specific groups such as unemployed people, 5,6 veterans, 7 youths, 8 women, 9 and the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of expectation and disorientation, a sense of waste and failure because of unemployment, stigma and shame were major issues that affected the mentality of unemployed graduates in this study and Cockshott et al (2021) suggested to have counselling services in universities that can better manage the transition to the employment of graduates. In addition to this, Khezri et al (2020) claimed that, unemployed graduates' became anti-social due to the influence of unemployment and it is considered a threat to social and political development.…”
Section: Introductionmentioning
confidence: 99%